Structure, Reliability, Measurement Stability, and Construct Validity of the Polish Version of the Revised Child Anxiety and Depression Scale. (December 2019) - Skoczeń, Ilona; Rogoza, Radosław; Rogoza, Marta; Ebesutani, Chad; Chorpita, Bruce
The Revised Child Anxiety and Depression Scale (RCADS) is a self-report questionnaire that aims to assess symptoms of anxiety and depressive disorders in children. Two studies were conducted to evaluate the psychometric properties of the Polish version of the RCADS. Study 1 was conducted to analyze the structural validity and reliability of the RCADS scores and Study 2 assessed the longitudinal measurement of stability over time. Data were collected from a community sample of 501 children and adolescents aged 8 to 14 years in Poland. The original 47-item version of the Polish RCADS was compared with two shortened versions: 30- and 20-item versions. Overall results revealed support for the structural and construct validity, reliability, and stability of the Polish version of the RCADS.